2013
DOI: 10.1152/ajpcell.00361.2012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal serotonin transporter expression via epigenetic mechanisms: role of HDAC2

Abstract: The serotonin (5-HT) transporter (SERT) facilitates clearance of extracellular 5-HT by its uptake and internalization. Decreased expression of SERT and consequent high 5-HT levels have been implicated in various diarrheal disorders. Thus, appropriate regulation of SERT is critical for maintenance of 5-HT homeostasis in health and disease. Previous studies demonstrated that SERT is regulated via posttranslational and transcriptional mechanisms. However, the role of epigenetic mechanisms in SERT regulation is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Foley et al reported that interferon‐γ and tumor necrosis factor‐α downregulated SERT expression in colonic epithelial cells in vitro , while another report also demonstrated that enteropathogenic E. coli infection inhibits intestinal SERT function and expression . Moreover, Gill et al indicated a novel mechanism of downregulation of intestinal SERT by epigenetic mechanisms involving histone deacetylase2 inhibition . Although SERT expression may be regulated by such mechanisms, additional details should be clarified by further examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Foley et al reported that interferon‐γ and tumor necrosis factor‐α downregulated SERT expression in colonic epithelial cells in vitro , while another report also demonstrated that enteropathogenic E. coli infection inhibits intestinal SERT function and expression . Moreover, Gill et al indicated a novel mechanism of downregulation of intestinal SERT by epigenetic mechanisms involving histone deacetylase2 inhibition . Although SERT expression may be regulated by such mechanisms, additional details should be clarified by further examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Control experiments were performed by the addition of DMSO solvent (Sigma-Aldrich) and following the same procedure. Cell line treatments with histone deacetylase (HDAC) inhibitor trichostatin A (TSA) (Selleck Chemicals, Houston, TX, USA) were carried out at 1 lM concentration for 24 h as previously published (Gill et al, 2013). Control experiments were treated by the addition of solvent alone.…”
Section: Inhibition Of Dna Methylation and Histone Deacetylation In Cmentioning
confidence: 99%
“…Some prior publications have suggested that SERT is down-regulated in some inflammatory or diarrheal motility disorders. 9,18 We hypothesized that SERT expression would be altered in the group of dogs with chronic enteropathy. It has previously been reported that mRNA-encoding SERT and SERT protein are diminished in an animal model of colitis.…”
Section: Discussionmentioning
confidence: 99%